Head Lice Mortality Activity (Pediculushumanus capitis) After Treating with Combination of Soursop Leaves Extract and Eucalyptus Oil - HAMNA FATHIA ZAHRA; DITA PRATIWI KUSUMA WARDANI; ISNA HIKMAWATI; ATIKA NUR AZIZAH; IKHSAN MUJAHID; Muhammad Luthfi Almanfaluthi; OEI STEFANI YUANITA WIDODO; RETNO SULISTIYOWATI (Jurnal Veteriner, 2025)
Pediculosis capitis is a scalp infection caused by the obligate ectoparasite Pediculus humanus capitis. This condition can be treated through various methods, including the use of medications. Soursop leaf extract and eucalyptus oil are known to exhibit lethal activity against P.h. capitis due to the presence of acetogenins, isoflavones, and cineole. This study aims to investigate the mortality activity of P.h. capitis following treatment with a combination of soursop leaf extract and eucalyptus oil. The study employed a true experimental design, specifically a post-test-only control group design, comprising two control groups (1% permethrin as the positive control (K+) and distilled water as the negative control (K-)) and five treatment groups with combinations of 5% soursop leaf extract and 5% eucalyptus oil (P1=1:1, P2=1:2, P3=2:1, P4=1:3, P5=3:1). The effectiveness of the combinations on P.h. capitis mortality was analyzed using Friedman, while the LC50 and LT50 values were determined through probit analysis. The results showed significant differences in mortality rates between the negative control group and the positive control group, as well as all treatment groups. Significant differences were also observed between the positive control group and the treatment groups P3, P4, and P5. However, no significant differences were found among the treatment groups at various observation times. The treatment results of group P2 (1:2) were the most effective in killing P. h. capitis. The combination of soursop leaf extract and eucalyptus oil has been proven effective as a natural pediculicide.